The Biology of Sea Turtles, Volume II - Lutz, Peter (CRC Press, 2009)
The success of the first volume of The Biology of Sea Turtles revealed a need for broad but comprehensive reviews of major recent advances in sea turtle biology. Biology of Sea Turtles, Volume II emphasizes practical aspects of biology that relate to sea turtle management and to changes in marine and coastal ecosystems. These topics include the interactions of humans and sea turtles, an introduction to sea turtle anatomy, sensory and reproductive biology, sea turtle habitat use and ecology, stress and health, and the maintenance of captured animals. This volume provides both historical and up-to-date information.